Psychological aspects of patients with intestinal stoma: integrative review - Natália Michelato Silva; Manoel Antônio dos Santos; Sara Rodrigues Rosado; Cristina Maria Galvão; Helena Megumi Sonobe (Universidade de São Paulo, 2017)
ABSTRACT Objective: to analyze evidences of psychological aspects of patients with intestinal stoma. Method: integrative review with search of primary studies in the PsycINFO, PubMed, CINAHL and WOS databases and in the SciELO periodicals portal. Inclusion criteria were: primary studies published in a ten-year period, in Portuguese, Spanish or English, available in full length and addressing the theme of the review. Results: after analytical reading, 27 primary studies were selected and results pointed out the need to approach patients before surgery to prevent the complications, anxieties and fears generated by the stoma. The national and international scientific production on the experience of stomized patients in the perioperative moments is scarce. Conclusion: it is recomendable that health professionals invest in research on interventions aimed at the main psychological demands of stomized patients in the perioperative period, respecting their autonomy on the decisions to be made regarding their health/illness state and treatments.